The Change of Perinatal Mortality Over Three Decades in a Reference Centre in the Aegean Region: Neonatal Mortality has decreased but Foetal Mortality Remains Unchanged - Nilgün Kültürsay (Balkan Medical Journal, 2017)
Background: Perinatal, foetal and neonatal mortality statistics are important to show the development of a health care system in a country. However, in our country there are very few national and regional data about the changing pattern of perinatal neonatal mortality along with the development of new technologies in this area. Aims: Evaluation of the changes in mortality rates and the causes of perinatal and neonatal deaths within years in a perinatal reference centre which serves a high-risk population. Study Design: Cross-sectional retrospective study. Methods: The perinatal, neonatal and foetal mortality rates in the years 1979-1980 (1st time point) and 1988-1989 (2nd time point) were compared with the year 2008 (3rd time point). The causes of mortality were assessed by Wigglesworth classification and death reports. The neonatal mortality in the neonatal intensive care unit was also calculated. Results: Foetal mortality rates were 44/1000, 31.4/1000 and 41.75/1000 births, perinatal mortality rates were 35.6/1000, 18.8/1000 and 9/1000 births, and neonatal mortality rates were 35.6/1000, 18.8/1000 and 9/1000 live births for the three study time points, respectively. The mortality rate in neonatal intensive care unit decreased consistently from 33%, to 22.6% and 10%, respectively, together with decreasing neonatal mortality rates. The causes of perinatal deaths were foetal death 85%, immaturity 4%, and lethal congenital malformations 8% according to Wigglesworth classification in 2008, showing the high impact of foetal deaths on this high perinatal mortality rate. Infectious causes of neonatal deaths decreased but congenital anomalies increased in the last decades. Conclusion: Although neonatal mortality rate decreased significantly; foetal mortality rate has stayed unchanged since the late eighties. In order to decrease foetal and perinatal mortality rates more efficiently, reducing consanguineous marriages and providing better antenatal care for high risk pregnancies are needed